How do we make sense of the thesis “bai (white) ma (horse) fei (is not) ma (horse)”? - Yang, Xiaomei (Dao, 2019)
In this article, I introduce a new interpretation of the puzzling thesis “bai 白 (white) ma 馬 (horse) fei 非 (is not) ma 馬 (horse)” argued by Gongsun Long 公孫龍 in his essay “On White Horse (Bai Ma Lun 白馬論).” I argue that previous interpretations, which can be grouped under the name of “attribute-object interpretations,” are not satisfactory, and that the thesis on the new interpretation is not about attributes or objects, but about names. My argument focuses on the disagreement over inseparability of white (shou bai zhi zheng 守白之爭) between Gongsun Long and his interlocutor in the text of “On White Horse.” On my interpretation or the name interpretation, the disagreement is about whether constituents of a syntactically complex or multi-term name are separable or have their contextually independent meanings. Gongsun Long’s thesis makes perfect sense on my interpretation, and is supported by the text and other preserved texts collected in GongsunLong Zi 公孫龍子. The name interpretation can also make sense of some puzzling expressions of sophists in the classic period.
Keywords: Complex name; Descriptive phrase; Inseparability of white; Simple name; White Horse; dept.phi; peer-reviewed

How to make sense of the claim “True knowledge is what constitutes action”: A new interpretation of wang yangming’s doctrine of unity of knowledge and action - Yang, Xiaomei (Dao-a Journal of Comparative Philosophy, 2009)
No one denies the importance of applying knowledge to actions. But claiming identity (unity) of knowledge and action is quite another thing. There seem to be two problems with the claim: (1) the identity claim implies that the sole cause for one to fail to act on what one judges to be right is ignorance, but it is obviously false that the sole cause of failure in moral actions is ignorance. (2) The identity statement implies non-separation of knowledge and action. But knowledge does not necessarily lead to action. However, the identity of knowledge and action is what a famous Ming Confucian scholar, Wang Yang-ming, proposed and the concept became the central doctrine of his teaching. Though there are several major interpretations of Wang's doctrine in contemporary literature, it is not clear to me how they deal with the above mentioned difficulties. In this article, I will discuss these interpretations of the doctrine and propose a new interpretation. My purpose is to give an interpretation of Wang's doctrine that has the capacity of dealing with these challenges to the doctrine and also captures the essence of his teaching. © 2009 Springer Science+Business Media B.V.
Keywords: Action; Chinese philosophy; Moral knowledge (liang zhi); Neo-confucianism; dept.phi; peer-reviewed

Some issues in Chinese philosophy of religion - Yang, Xiaomei (Philosophy Compass, 2008)
Keywords: dept.phi

The problem of evil in the Neo-Confucian context: Wang Yangming’s view on evil - Yang, Xiaomei (Asian Philosophy, 2020)
Wang Yangming believes that human nature is entirely good. A question naturally arises: where is evil from? It has been argued that Wang’s idealism gives rise to the problem of evil. I first argue that the difficulty for Wang to have a coherent account of evil can be removed when his idealism is understood in a narrow sense. Second, I offer an account of Wang’s view on evil in three steps. First, I argue that evil comes from the interaction between humans and the external world according to Wang. Second, I show that given Wang’s account of human nature with three aspects, there is no contradiction between Wang’s claim that human nature is the same in everyone and Wang’s claim about differences in our natural endowment which affect our moral practice. Third, I argue that Wang’s doctrine of non-distinction of good and evil in the original substance of human nature is uniquely Confucian. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Human nature; dept.phi; idealism; origin of evil; peer-reviewed; physical nature

Reframing the issue in 13.18 of the analects of Confucius: family privileges in criminal litigation and the Confucian insight - Yang, Xiaomei (Dao, 2024)
The sheep case in Analects 13.18 has generated a heated debate in contemporary Chinese philosophy for more than a decade. One side in this debate criticizes Confucius’ view in the sheep case and the other side defends Confucius’ position. Neither side’s reading of 13.18 is satisfactory. I argue that something important in the text has been overlooked and this omission may explain why neither side gives a satisfying reading. I offer in this essay a new reading of the sheep case which pays attention to what the existent interpretations have overlooked in the text. This new focus will give us a new perspective to reframe the issue in question and to defend the Confucian position in a more convincing way. On the new interpretation, Confucius’ position in the sheep case suggests a sensible and reasonable way for the state to balance some important social interests which the state seeks to protect.
Keywords: Criminal prosecution; Family privilege; Filial piety; Sheep case; dept.phi; peer-reviewed